2007
DOI: 10.2341/06-141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Postoperative Sensitivity in Posterior Composite Restorations

Abstract: This incidence of postoperative sensitivity was evaluated in resin-based posterior restorations. Two hundred and ninety-two direct restorations were evaluated in premolars and molars. A total of 143 Class I and 149 Class II restorations (MO/OD and MOD) were placed in patients ranging in age from 30 to 50 years. After the cavity preparations were completed, a rubber dam was placed, and the preparations were restored using a total-etch system (Prime & Bond NT) and a resin-based restorative material (TPH Spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…1 The role of composite polymerization stress as one of the main causes of marginal integrity loss and consequent post-operative occurrences, such as hypersensitivity, microleakage and secondary caries, has been described in some studies. [2][3] Stress magnitude is related to the restorative technique employed, as well as to the composite composition and degree of conversion. One of the factors associated with the restorative procedure is the restoration's bonded-to-unbonded surface area (cavity configuration factor or C-factor).…”
Section: Introductionmentioning
confidence: 99%
“…1 The role of composite polymerization stress as one of the main causes of marginal integrity loss and consequent post-operative occurrences, such as hypersensitivity, microleakage and secondary caries, has been described in some studies. [2][3] Stress magnitude is related to the restorative technique employed, as well as to the composite composition and degree of conversion. One of the factors associated with the restorative procedure is the restoration's bonded-to-unbonded surface area (cavity configuration factor or C-factor).…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed in our study that the percentage of POS is more in Class II than Class I cavities but without signifi cant diff erence, that might be related to more removal of tooth structure in Class II and more exposure of the dentinal tubules. Another study [14] also found that POS is more in Class II and it is related to the complexity of the preparation design. In relation to cavity depth and POS, this study shows that POS in deep cavity is more than medium and shallow cavities, that might be the result of pulp injury from deep preparation, and also the diameter of the dentinal tubules near the pulp is more than the diameter near the dentine enamel junction.…”
Section: Discussionmentioning
confidence: 99%
“…This has been one of the most reported clinical problems after the final cementation of indirect restorations [2][3][4]. The dentinal fluid is within the dentinal tubules and contains a great amount of water and odontoblastic processes [5].…”
Section: Introductionmentioning
confidence: 99%